Role of Pyroptosis and Ferroptosis in the Progression of Atherosclerotic Plaques - Yang, Zhen; Shi, Junhe; Chen, Li; Fu, Changgeng; Shi, Dazhuo; Qu, Hua (Frontiers in Cell and Developmental Biology, 2022)
Pyroptosis is a special way of programmed cell death which is dependent on the activation of cysteinyl aspartate specific proteinase 1 (Caspase-1) and Caspase-4/5/11. Ferroptosis is an iron-dependent cell death that characterized by the intra-cellular lipid peroxidation-mediated membrane damage. Pyroptosis or ferroptosis in macrophages, smooth muscle cells, and vascular endothelial cells are believed to be closely related to the progression of atherosclerotic plaques. Therefore, we discuss the role of pyroptosis and ferroptosis in the development of atherosclerotic plaques and may provide new strategies for the treatment of atherosclerosis.